Comprehensive health risk assessment of urban ambient air pollution (PM2.5, NO2 and O3) in Ghana - Boansi Adu Ababio; Gerheart Winfred Ashong; Thomas Peprah Agyekum; Blessed Adjei Yeboah; Marian Asantewah Nkansah; Jonathan Nartey Hogarh; Michael Kweku Commeh; Edward Ebow Kwaansa-Ansah; Kwabena Dabie; Felix Adulley; Eldad Boansi; Lorenda Sarbeng; et al. (Ecotoxicology and Environmental Safety)
Urbanization and industrialization have drastically increased ambient air pollution in urban areas globally from vehicle emissions, solid fuel combustion and industrial activities leading to some of the worst air quality conditions. Air pollution in Ghana causes approximately 28,000 premature deaths and disabilities annually, ranking as a leading cause of mortality and disability-adjusted life years. This study evaluated the annual concentrations of PM2.5, NO2 and O3 in the ambient air of 57 cities in Ghana for two decades using historical and forecasted data from satellite measurements. The study assessed urban air quality and evaluated both carcinogenic and non-carcinogenic health risks associated with human exposure to ambient air pollutants. Alarmingly, our findings revealed the yearly median PM2.5 concentrations (50.79–67.97 µg m−3) to be significantly higher than the WHO recommendation of 5 µg m−3. Tropospheric ozone concentrations (72.21–92.58 µg m−3 ) also exceeded the WHO annual standard of 60 µg m−3. Furthermore, NO2 concentrations (3.65–12.15 µg m−3 ) surpassed the WHO threshold of 10 µg/m³ in multiple cities. Hazard indices indicated that PM2.5 and O3 pose significant non-carcinogenic health risks for younger age groups for a daily exposure duration of three hours and beyond. According to the Air Quality Life Index (AQLI) in our study, exposure to PM2.5 shortens life expectancy by 4.5–6.2 years. The ambient air of the majority (98 %) of the cities was unhealthy for sensitive groups. This study reveals the urgent need for comprehensive air quality policies in Ghanaian cities. It emphasizes the significance of robust real-time monitoring of air pollutants and the investigation of seasonal dust storm effects, to fill data gaps in Ghana and West Africa, facilitating evidence-based interventions that improve urban air quality and public health outcomes.